2004
DOI: 10.1002/art.20066
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of disease features within 512 multicase rheumatoid arthritis families

Abstract: Objective. To determine whether specific rheumatoid arthritis (RA) disease features demonstrate the presence of significant familial clustering.Methods. We studied 1,097 individuals with RA from 512 multicase families enrolled in the North American Rheumatoid Arthritis Consortium. All patients were interviewed and examined to collect standardized information about demographic and clinical characteristics. Affected individuals also underwent radiography of the hands and wrists and were genotyped for the HLA-DRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 12 publications
1
37
0
3
Order By: Relevance
“…A full characterization of affected individuals and clinical parameters has been reported in 512 families from this collection. 36 The median age at onset for the affected population studied in the current report was 39 years, with an interquartile range of 30-49 years. The mean duration of disease in this population is 16 years with a median of 13 years.…”
Section: Resultsmentioning
confidence: 63%
“…A full characterization of affected individuals and clinical parameters has been reported in 512 families from this collection. 36 The median age at onset for the affected population studied in the current report was 39 years, with an interquartile range of 30-49 years. The mean duration of disease in this population is 16 years with a median of 13 years.…”
Section: Resultsmentioning
confidence: 63%
“…The majority of families included a single sibpair (88.4%), and the remaining families included 3 siblings (10.4%), 4 siblings (1%), or 6 siblings (0.2%). Details of our enrollment procedures have been published previously (1), and clinical and genetic marker data are available at http:// www.naracdata.org/index.asp. Briefly, eligible families had to meet the following criteria: Ն2 siblings satisfied the American College of Rheumatology (ACR; formerly, the American Rheumatism Association) 1987 criteria for RA (22), Ն1 sibling had documented erosions on hand radiographs, and Ն1 sibling had disease onset between the ages of 18 and 60 years.…”
Section: Methodsmentioning
confidence: 99%
“…The cases in the NARAC study population consisted of RA patients of self-reported white ancestry who were randomly drawn from four different sample groups of patients and controls were recruited from the New York Cancer Project. 24,25 All these studies were conducted after obtaining approval from the Regional Ethics Committees and in accordance with the Declaration of Helsinki.…”
Section: Study Populationmentioning
confidence: 99%